Coming of age with quantum information notes on a Paulian idea - Fuchs, Christopher A., 1964- (Cambridge University Press, 2011)
"A passionate and personal account of the early days of quantum information and quantum computing, this unique book is a collection of more than 500 letters between the author and many of the founders of these intriguing fields. Christopher A. Fuchs is one of the most penetrating modern thinkers on the philosophical foundations of quantum mechanics. This remarkable book follows his journey as he comes to grips with the quantum world. It contains correspondence with Charles Bennett, Gilles Brassard, Rolf Landauer, N. David Mermin, Michael Nielsen, Asher Peres, John Preskill, Abner Shimony, William Wootters, Anton Zeilinger, and many others. Filled with diary entries, anecdotes, historical selections, and research ideas, this book will fascinate physicists, philosophers, and historians of science"--